Metodologias de ensino: uma análise a partir da observação no estágio de ensino fundamental em uma escola da rede pública de Santarém - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The present work focuses on Teaching Methodologies: An Analysis Based on Observation during a Fundamental Education Internship at a Public School in Santarém. This study is the result of participatory observation conducted during the internship in fundamental education, carried out in a public school in the urban area of Santarém-Pará, from February to May 2024. The research focused on the teaching methodology employed by the head teacher of a 5th-grade class. The primary objective was to analyze the pedagogical strategies used by the teacher and identify the main difficulties encountered in the teaching-learning process. The methodology adopted had both theoretical and practical aspects. Initially, the field internship was conducted, followed by the preparation of a report that served as the basis for the experience narratives. The theoretical part included mapping the main methodologies applied in the classroom. During the observation, it was found that the head teacher faced several challenges, which hindered the implementation of new methodologies due to the lack of support and proper training. This scenario led the teacher to rely on traditional methods, with few activities that deviated from this approach. Such a reality is not much different from what is observed in other public schools. The observations made throughout this study highlight the importance of continuous teacher training and school management support to address the challenges and diversity present in the classroom. The partnership between teachers and management is essential to meet the needs of the school institution. The work is structured in two chapters. The first presents the concepts of different teaching methods and their importance, as well as contributions from authors such as Herbart, Piaget, Vygotsky, Montessori, Freire, and Saviani, who discuss teaching practices. The second part presents the experiences based on the mandatory internship in the 5th-grade class, comparing theory with practice and addressing how the head teacher applied different methods in the classroom.
Keywords: Metodologias de Ensino; Desafios; Observação Participativa; Formação Docente; CNPQ:: CIÊNCIAS HUMANAS